One-dimensional 2H-phase MoS < 1.5 > X < 0.5 > nanowire material, and preparation method, application and battery thereof

The Mo2S3 nanowires were vulcanized with the chalcogen element X element by solid phase synthesis to prepare the 2H phase MoS1.5X0.5 nanowires, which solved the problem of complex and difficult to prepare on a large scale in the prior art, and achieved efficient and uniform nanowire preparation and excellent electrochemical properties.

CN119650690AActive Publication Date: 2025-03-18SHANGHAI JIAOTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411852916.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The preparation method of one-dimensional layered transition metal chalcogenide nanowires in the prior art is complex and difficult to prepare on a large scale, which limits its application.

Method used

By solid phase synthesis, Mo2S3 nanowires were vulcanized with chalcogen element X element to prepare 2H phase MoS1.5X0.5 nanowires. This method is simple, the reaction source is environmentally friendly and easy to produce in industrial use.

Benefits of technology

The obtained MoS1.5X0.5 nanowire has uniform morphology and high single crystallinity. It has excellent electrochemical properties when applied to sodium ion batteries, solving the problem of complex preparation and difficulty in large-scale preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650690A_ABST
    Figure CN119650690A_ABST
Patent Text Reader

Abstract

The invention discloses a one-dimensional 2H-phase MoS < 1.5 > X < 0.5 > nanowire material as well as a preparation method, application and a battery thereof. The preparation method comprises the following steps: placing a mixture containing a Mo2S3 nanowire and an X elementary substance in a reaction tube, vacuumizing and sealing the reaction tube, and calcining at 350-1000 DEG C for 2-20 hours to prepare the one-dimensional 2H-phase MoS < 1.5 > X < 0.5 > nanowire material, wherein X is one or more of S, Se and Te. The preparation method disclosed by the invention is simple, a reaction source is environment-friendly, industrial production is easy, and the prepared one-dimensional 2H-phase MoS < 1.5 > X < 0.5 > nanowire material is uniform in form and high in single crystal property, and has excellent electrochemical performance when being applied to a sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a one-dimensional 2H phase MoS 1.5 X 0.5 Nanowire materials and their preparation methods, applications and batteries. Background Art

[0002] In recent years, one-dimensional nanomaterials have been the research focus in the field of nanomaterials and are one of the material foundations of future high technology. One-dimensional nanomaterials are widely used in electronic devices, photonic devices, photoelectrochemistry, and energy storage and conversion due to their unique size effects and tunable electronic and optical properties. Layered transition metal chalcogenides are a typical class of low-dimensional materials with rich chemical compositions and physical properties. Among them, one-dimensional MoS2 nanomaterials have high ionic and electronic conductivity and have great potential for energy storage applications. However, due to the high symmetry space group P63 / mmc of MoS2 itself, it exhibits isotropy within the MoS2 plane, making it tend to grow into triangular or hexagonal sheets rather than one-dimensional lines during the growth process. At present, the common preparation methods of one-dimensional MoS2 nanomaterials mainly include top-down strategies represented by chemical exfoliation and bottom-up strategies represented by chemical vapor deposition. However, they often have the problem of complex preparation and difficulty in large-scale preparation. Therefore, one-dimensional layered transition metal chalcogenide nanowires are limited by their crystal structure and their controllable preparation is a huge challenge. Summary of the invention

[0003] The technical problem solved by the present invention is to overcome the defects of the prior art that the preparation method of one-dimensional layered transition metal chalcogenide nanowires is complicated and difficult to prepare on a large scale, and to provide a one-dimensional 2H phase MoS 1.5 X 0.5 Nanowire material and its preparation method, application and battery. The preparation method of the invention is simple, the reaction source is environmentally friendly, and it is easy to industrialize. The prepared one-dimensional 2H phase MoS 1.5 X 0.5 The nanowire material has uniform morphology and high single crystallinity, and has excellent electrochemical properties when used in sodium ion batteries.

[0004] In the present invention, Mo2S3 nanowires are subjected to a sulfurization reaction with a chalcogen element X (X = S, Se, Te) by a solid phase synthesis method, thereby preparing 2H phase MoS 1.5 X 0.5 During the reaction, the chalcogen element X is transformed into a gas at high temperature and reacts with the Mo2S3 nanowire, thereby converting it into 2H phase MoS 1.5 X 0.5 Nanowires.

[0005] The present invention solves the above technical problems through the following technical solutions:

[0006] The present invention provides a one-dimensional 2H phase MoS 1.5 X 0.5 A method for preparing a nanowire material comprises the following steps:

[0007] A mixture containing Mo2S3 nanowires and X single substance is placed in a reaction tube, the reaction tube is evacuated and sealed, and then calcined at 350-1000°C for 2-20h to obtain the one-dimensional 2H phase MoS 1.5 X 0.5 Nanowire material; wherein X is one or more of S, Se and Te.

[0008] In the present invention, the molar ratio of the X element to the Mo2S3 nanowire is preferably not less than 1, more preferably 1-1.2, such as 1 or 1.1. When the amount of the X element is too small, the Mo2S3 conversion is incomplete, and MoS 1.5 X 0.5 Nanowires.

[0009] In the present invention, the preparation method of the mixture containing Mo2S3 nanowires and X single substance can be conventional in the art, for example, the mixture is obtained by grinding the Mo2S3 nanowires and X single substance uniformly. The grinding is generally performed in an air atmosphere.

[0010] In the present invention, the reaction tube is preferably a quartz tube.

[0011] In the present invention, after the vacuuming, the vacuum degree of the reaction tube is preferably less than or equal to 10 -3 Pa.

[0012] In the present invention, according to the common practice in the art, after the vacuuming, the tube can generally be sealed by a quartz column to achieve sealing.

[0013] In the present invention, the calcination is generally carried out in a muffle furnace.

[0014] In the present invention, the rate of increasing the temperature to the calcination temperature may be 120-300° C. / h, for example 160° C. / h.

[0015] In the present invention, the calcination temperature is preferably 500-900°C, such as 500°C, 600°C or 700°C.

[0016] In the present invention, the calcination time is preferably 3-12 hours, such as 3 hours, 5 hours or 10 hours.

[0017] In certain embodiments, when X is Se and / or Te, the calcination temperature is 600-750° C., and the calcination time is 3-12 h.

[0018] In certain embodiments, when X is Te, the calcination temperature is 600-750° C., and the calcination time is 8-12 h.

[0019] In the present invention, during the calcination, it is generally necessary to place the end of the reaction tube where the mixed powder is placed in a preset temperature zone and keep the temperature at a preset temperature for a preset time.

[0020] In the present invention, according to the common practice in the art, after the calcination is completed, it is generally necessary to cool naturally to room temperature.

[0021] In the present invention, the diameter of the Mo2S3 nanowire may be 100-600 nm, and the length of the Mo2S3 nanowire may be 50-200 μm.

[0022] In the present invention, the Mo2S3 nanowires can be obtained from conventional commercial sources or prepared by conventional methods in the art, such as by solid phase synthesis.

[0023] In the present invention, the preparation method of the Mo2S3 nanowires preferably includes the following steps: placing a mixture of molybdenum powder, sulfur powder, red phosphorus and sodium chloride in a quartz tube, evacuating and sealing the quartz tube, calcining at 750-1200°C for 20-48h, and then washing and drying.

[0024] The molybdenum powder and the sulfur powder are generally added in a stoichiometric ratio, for example, 2:3.

[0025] The mass of the red phosphorus is preferably 2%-10% of the sum of the mass of the molybdenum powder and the sulfur powder, preferably 3%-8%, for example 5%.

[0026] The mass of the sodium chloride is preferably 3-8 times, for example 5 times, the sum of the mass of the molybdenum powder and the sulfur powder.

[0027] The preparation method of the mixture can be conventional in the art, for example, molybdenum powder, sulfur powder, red phosphorus and sodium chloride are ground evenly, or molybdenum powder and sulfur powder are first mixed and then red phosphorus and sodium chloride are added and ground.

[0028] The calcination is generally carried out in a muffle furnace. The calcination temperature is preferably 800-1100° C., such as 950° C. The calcination time is preferably 24-48 hours, such as 33.3 hours.

[0029] The washing solvent may be conventional in the art, such as deionized water. The drying method may be conventional in the art, such as drying. The drying temperature may be 80-120° C., such as 100° C. The drying time may be 6-24 hours, such as 12 hours.

[0030] The present invention also provides a one-dimensional 2H phase MoS prepared by the preparation method as described above. 1.5 X 0.5 Nanowire materials.

[0031] The present invention also provides a one-dimensional 2H phase MoS 1.5 X 0.5 Nanowire material, X is one or more of S, Se and Te, the MoS 1.5 X 0.5 The diameter of the nanowires is 100-800nm ​​and the length is 50-200μm.

[0032] In the present invention, the one-dimensional 2H phase MoS 1.5 X 0.5 The diameter of the nanowire material is preferably 200-400 nm, such as 200 nm, 300 nm or 400 nm.

[0033] In the present invention, the one-dimensional 2H phase MoS 1.5 X 0.5 The length of the nanowire material is preferably 100-150 μm, such as 100 μm, 120 μm or 150 μm.

[0034] The present invention also provides a one-dimensional 2H phase MoS as described above 1.5 X 0.5 Application of nanowire materials in sodium-ion batteries.

[0035] The present invention also provides a sodium ion battery, which comprises the one-dimensional 2H phase MoS 1.5 X 0.5 Nanowire materials.

[0036] In the present invention, in the sodium ion battery, the one-dimensional 2H phase MoS 1.5 X 0.5 The nanowire material is preferably used as a negative electrode material.

[0037] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0038] The reagents and raw materials used in the present invention are commercially available.

[0039] The positive and progressive effects of the present invention are:

[0040] The present invention successfully prepared a one-dimensional 2H phase structure of MoS by using the in-situ topological phase transition reaction of Mo2S3 nanowires for the first time. 1.5 X 0.5 Nanowires make up for the MoS 1.5 X 0.5 The preparation method provided by the present invention has simple steps, short growth cycle and high success rate (~100%). 1.5 X 0.5 The nanowires are numerous, have a high aspect ratio, are uniform in morphology, and are highly crystalline. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The structure of the quartz tube and the placement position of the raw materials in the quartz tube in the embodiment of the present invention;

[0042] Figure 2 This is an optical photograph of the 2H phase MoS2 nanowires prepared in Example 1;

[0043] Figure 3 This is a scanning electron microscope image of the 2H phase MoS2 nanowires prepared in Example 1;

[0044] Figure 4 XRD pattern of 2H phase MoS2 nanowires prepared in Example 1;

[0045] Figure 5 This is the Raman image of the 2H phase MoS2 nanowires prepared in Example 1.

[0046] Figure 6 The MoS prepared in Example 2 1.5 Se 0.5 SEM images of nanowires;

[0047] Figure 7 The MoS prepared in Example 2 1.5 Se 0.5 XRD pattern of nanowires;

[0048] Figure 8 The MoS prepared in Example 2 1.5 Se 0.5 Raman images of nanowires;

[0049] Fig. 9 The MoS prepared in Example 3 1.5 Te 0.5 SEM images of nanowires;

[0050] Fig.10 The MoS prepared in Example 3 1.5 Te 0.5 XRD pattern of nanowires;

[0051] Fig.11 The MoS prepared in Example 3 1.5 Te 0.5 Raman images of nanowires;

[0052] Fig.12 This is the XRD pattern of the nanowires prepared in Comparative Example 1;

[0053] Fig.13 This is the XRD pattern of the nanowires prepared in Comparative Example 2;

[0054] Fig.14 This is a small current cycling performance diagram of the 2H phase MoS2 nanowire prepared in Example 1;

[0055] Fig.15 This is a rate performance diagram of 2H phase MoS2 nanowires prepared in Example 1;

[0056] Fig.16 This is the long cycle test diagram of the 2H phase MoS2 nanowires prepared in Example 1. DETAILED DESCRIPTION

[0057] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0058] The preparation method of Mo2S3 nanowires used in the following examples is:

[0059] After mixing high-purity molybdenum powder (purity of 99.9%) and high-purity sulfur powder (purity of 99.99%) in a molar ratio of 2:3, red phosphorus and sodium chloride powder (purity of 99.9%) are added, ground and mixed thoroughly to obtain a mixed powder, and the mixed powder is placed in a quartz tube; wherein the mass of the red phosphorus is 5% of the sum of the mass of the molybdenum powder and the sulfur powder, and the mass of the sodium chloride powder is 5 times the sum of the mass of the molybdenum powder and the sulfur powder;

[0060] The quartz tube containing the mixed powder was evacuated and sealed, placed in a muffle furnace, heated to 950°C at a rate of 120°C / h and kept warm for 2000 minutes, then stopped heating and cooled naturally to room temperature to obtain a product, which was washed with water, filtered, and dried at 100°C for 12 hours to obtain Mo2S3 nanowires. The prepared Mo2S3 nanowires have a diameter of 300-500nm and a length of 50-150μm.

[0061] Example 1

[0062] (1) grinding and fully mixing Mo2S3 nanowires and elemental sulfur in air to obtain a mixed powder, wherein the molar ratio of Mo2S3 nanowires to elemental sulfur is 1:1;

[0063] (2) Place the mixed powder into one end of a quartz tube and evacuate the tube so that the pressure at the tube mouth is less than 10 -3 Pa, and seal the tube; put the quartz tube into a muffle furnace, heat the muffle furnace to 500°C at a rate of 160°C / h and keep it warm for 3h, then stop heating, let the muffle furnace cool naturally to room temperature, and obtain good quality 2H phase MoS2 nanowires at one end of the quartz tube where the mixed powder is placed.

[0064] Example 2

[0065] (1) grinding and fully mixing Mo2S3 nanowires and elemental selenium in air to obtain a mixed powder, wherein the molar ratio of Mo2S3 nanowires to elemental selenium is 1:1;

[0066] (2) Place the mixed powder into one end of a quartz tube and evacuate the tube so that the pressure at the tube mouth is less than 10 -3 Pa, and seal the tube; put the quartz tube into the muffle furnace, heat the muffle furnace to 700℃ at a rate of 160℃ / h and keep it warm for 3h, then stop heating, let the muffle furnace cool naturally to room temperature, and place the mixed powder at one end of the quartz tube to obtain MoS with good quality. 1.5 Se 0.5 Nanowires.

[0067] Example 3

[0068] (1) grinding and fully mixing Mo2S3 nanowires and elemental tellurium in air to obtain a mixed powder, wherein the molar ratio of Mo2S3 nanowires to elemental tellurium is 1:1;

[0069] (2) Place the mixed powder into one end of a quartz tube and evacuate the tube so that the pressure at the tube mouth is less than 10 -3 Pa, and seal the tube; put the quartz tube into the muffle furnace, heat the muffle furnace to 700℃ at a rate of 160℃ / h and keep it warm for 10h, then stop heating, let the muffle furnace cool naturally to room temperature, and place the mixed powder at one end of the quartz tube to obtain MoS with good quality. 1.5 Te 0.5 Nanowires.

[0070] Comparative Example 1

[0071] Compared with Example 1, except that the calcination temperature in step (2) is adjusted to 300° C., the other parameters and conditions are the same as those in Example 1.

[0072] Comparative Example 2

[0073] Compared with Example 1, except that the insulation time in step (2) is adjusted to 1 h, the other parameters and conditions are the same as those in Example 1.

[0074] Effect Example

[0075] (1) Morphology and structure characterization

[0076] Figure 1 The structure of the quartz tube in the embodiment of the present invention and the method for preparing MoS 1.5 X 0.5 Nanowires are where the reaction materials are placed in the quartz tube.

[0077] The actual picture of the 2H phase MoS2 nanowire prepared in Example 1 is as follows Figure 2 As shown in FIG. 1 , it appears as gray-black powder clusters; its SEM image is shown in FIG. Figure 3 As shown in the figure, it can be seen that the length of the 2H phase MoS2 nanowire is about 150μm and the diameter is 400nm; its XRD Figure 4 As shown, it can be seen that the prepared MoS2 is 2H phase; its Raman diagram is as follows Figure 5 As shown, the typical E 2g and A 1g The peak also proves that MoS2 is 2H phase.

[0078] MoS prepared in Example 2 1.5 Se 0.5 SEM images of nanowires Figure 6 As shown in the figure, it can be seen that MoS 1.5 Se 0.5 The length of the nanowire is about 100 μm and the diameter is 200 nm; its XRD Figure 7 As shown, it can be seen that the prepared material is MoS 1.5 Se 0.5 Its Raman diagram is as follows Figure 8 shown.

[0079] MoS prepared in Example 3 1.5 Te 0.5 SEM images of nanowires Fig. 9 As shown in the figure, it can be seen that MoS 1.5 Te 0.5 The length of the nanowire is about 100 μm and the diameter is 400 nm; its XRD Fig.10 As shown, it can be seen that the prepared material is MoS 1.5 Te 0.5 Its Raman diagram is as follows Fig.11 shown.

[0080] The final product prepared in Comparative Example 1-2 was subjected to XRD test. Figure 12-13 As shown, it can be seen that what is prepared is a mixed phase of Mo2S3 and 2H phase MoS2, rather than pure 2H phase MoS2. It can be seen that when the calcination temperature is lower than 500℃ or the calcination time is lower than 3h, pure 2H phase MoS2 cannot be obtained.

[0081] (2) Electrochemical performance test

[0082] The electrochemical performance of the final products prepared in the above embodiments was evaluated using CR2032 button batteries.

[0083] The final product materials prepared in Examples 1-3, SuperP and polyvinylidene fluoride (PVDF) were uniformly mixed in a mass ratio of 8:1:1 to prepare an electrode slurry in NMP solvent. The electrode slurry was then evenly coated on a copper foil using a coating machine and dried overnight in a vacuum environment at 120°C. Finally, an anode sheet with a diameter of 13 mm was punched on a tablet press, and the loading amount was about 1-2 mg cm -2 The prepared electrode was used as the negative electrode, pure sodium as the counter electrode, GF / D glass fiber as the separator, and the organic electrolyte was 1.0M NaPF6 inDEGDME=100Vol%, and a CR2032 coin-type half-cell was assembled. The obtained battery was subjected to charge and discharge tests in an electrochemical workstation with a test voltage range of 0.01V-3.0V. The test results are shown in Table 1 and Figure 14-16 As shown:

[0084] Table 1

[0085] sample capacity High rate capacity Example 1 <![CDATA[705.2mAhg -1 @0.2Ag -1 ]]> <![CDATA[368.8mAhg -1 @10Ag -1 ]]> Example 2 <![CDATA[614.1mAhg -1 @0.2Ag -1 ]]> <![CDATA[378.2mAhg -1 @10Ag -1 ]]> Example 3 <![CDATA[516.4mAhg -1 @0.2Ag -1 ]]> <![CDATA[310.6mAhg -1 @10Ag -1 ]]>

[0086] Fig.14 The test results show that the 2H phase MoS2 nanowire sodium ion battery negative electrode exhibits 705.2mAh g -1 High capacity. Fig.15 The rate performance test results show that at 10A g -1 At a current density of 2H phase MoS2 nanowires, there is still 368.8 mAh g -1 Good rate performance. Fig.16 The cycle performance test results show that at 5A g -1 The 2H phase MoS2 nanowires have a long cycle life of 9700 cycles at a current density of .

[0087] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A one-dimensional 2H phase MoS 1.5 X 0.5 A method for preparing a nanowire material, characterized in that: It includes the following steps: A mixture containing Mo2S3 nanowires and X single substance is placed in a reaction tube, the reaction tube is evacuated and sealed, and then calcined at 350-1000°C for 2-20h to obtain the one-dimensional 2H phase MoS 1.5 X 0.5 Nanowire material; wherein X is one or more of S, Se and Te.

2. The one-dimensional 2H phase MoS according to claim 1 1.5 X 0.5 A method for preparing a nanowire material, characterized in that: The molar ratio of the X element to the Mo2S3 nanowire is not less than 1, preferably 1-1.2, such as 1 or 1.1; and / or, the calcination temperature is 500-900° C., such as 500° C., 600° C. or 700° C.; And / or, the calcination time is 3-12 h, such as 3 h, 5 h or 10 h.

3. The one-dimensional 2H phase MoS according to claim 1 1.5 X 0.5 A method for preparing a nanowire material, characterized in that: When X is Se and / or Te, the calcination temperature is 600-750° C., and the calcination time is 3-12 h; Preferably, when X is Te, the calcination temperature is 600-750° C., and the calcination time is 8-12 h.

4. The one-dimensional 2H phase MoS according to claim 1 1.5 X 0.5 A method for preparing a nanowire material, characterized in that: The diameter of the Mo2S3 nanowire is 100-600nm; And / or, the length of the Mo2S3 nanowire is 50-200 μm; And / or, the preparation method of the Mo2S3 nanowires comprises the following steps: placing a mixture of molybdenum powder, sulfur powder, red phosphorus and sodium chloride in a quartz tube, evacuating and sealing the quartz tube, calcining at 750-1200°C for 20-48h, and then washing and drying.

5. The one-dimensional 2H phase MoS as claimed in claim 4 1.5 X 0.5 A method for preparing a nanowire material, characterized in that: The preparation method of the Mo2S3 nanowires meets one or more of the following conditions: (1) The molar ratio of the molybdenum powder to the sulfur powder is 2:3; (2) The mass of the red phosphorus is 2% to 10% of the sum of the mass of the molybdenum powder and the sulfur powder; (3) The mass of the sodium chloride is 3-8 times the sum of the mass of the molybdenum powder and the sulfur powder; (4) The calcination temperature is 800-1100° C.; (5) The calcination time is 24-48 hours.

6. A one-dimensional 2H phase MoS 1.5 X 0.5 Nanowire material, characterized in that The preparation method is prepared according to any one of claims 1 to 5.

7. A one-dimensional 2H phase MoS 1.5 X 0.5 Nanowire material, characterized in that X is one or more of S, Se and Te, and the MoS 1.5 X 0.5 The diameter of the nanowires is 100-800nm ​​and the length is 50-200μm.

8. The one-dimensional 2H phase MoS as claimed in claim 7 1.5 X 0.5 Nanowire material, characterized in that The one-dimensional 2H phase MoS 1.5 X 0.5 The diameter of the nanowire material is 200-400nm; And / or, the one-dimensional 2H phase MoS 1.5 X 0.5 The length of the nanowire material is 100-150 μm.

9. A one-dimensional 2H phase MoS as claimed in any one of claims 6 to 8 1.5 X 0.5 Application of nanowire materials in sodium-ion batteries.

10. A sodium ion battery, characterized in that: It includes the one-dimensional 2H phase MoS as described in any one of claims 6-8 1.5 X 0.5 Nanowire materials; Preferably, the one-dimensional 2H phase MoS 1.5 X 0.5 Nanowire materials are used as negative electrode materials.

Citation Information

Patent Citations

  • Transitional metal chalcogenide nanowire and preparation method and energy storage application thereof

    CN104085923A

  • MoS&lt;x&gt;Se&lt;2-x&gt; / graphene anode material with layered structure, and preparation method thereof

    CN108346783A

  • High-conductivity high-length-diameter-ratio sulfide nanowire as well as preparation method and application thereof

    CN117766192A